Indirect ELISA using recombinant nonstructural protein 3D to detect foot and mouth disease virus infection associated antibodies. Issue 1 (January 2015) - Mahajan, Sonalika; Mohapatra, Jajati Keshari; Pandey, Laxmi Kant; Sharma, Gaurav Kumar; Pattnaik, Bramhadev
Abstract Foot-and-mouth disease (FMD) is a highly infectious disease of transboundary importance. Routine biannual vaccination along with surveillance activities is seen as the principal to control FMD in India. Non-structural protein (NSP) based immunoassays are the test of choice for the differentiation between infected and vaccinated population. In this study, 3D protein of FMD virus was expressed in Escherichia coli and an indirect ELISA (I-ELISA) was developed to detect 3D-antibodies in the infected bovines. 3D I-ELISA demonstrated comparable diagnostic sensitivity (97.6%) but lower specificity (80.8%) as compared to the in-house r3AB3 I-ELISA. However, the specificity values varied significantly for naïve and vaccinated samples and were observed to be 98.42% and 76.93%, respectively. A moderate degree of concordance (88.5%) was observed between the overall results of two ELISAs. 3D I-ELISA displayed a considerably lower specificity in uninfected vaccinated samples, thereby suggesting against its application for serosurveillance in intensively vaccinated population. However by virtue of its high diagnostic sensitivity and longer duration of persistence of 3D-antibody post-infection, 3D I-ELISA could be adopted for seroepidemiological investigations in regions not practicing vaccination and could be extended to susceptible species which are generally not covered by vaccination.